Religious education from minority cults: the case of the Hare Krishna in Madrid's city - Nuño Martínez, Néstor (Nómadas. Critical Journal of Social and Juridical Science, 2013)
Due to the little support in education that the spanish state brings to minority religions, these religions launch different kinds of educative strategies for their faithful. In this article there are analized through an anthropological approach different non-institucionalized educative activities that are launched from a Hare Krishna temple in the city of Madrid, showing how these activities that the temple's council proposes are loaded with a wide range of different meanings and interest that are builded by the subjects who come to them (both devouts and individuals that has no relation with it) and also the temple's council; an analisys that also can be used to the study of other complementary religious and cultural dimensions such as conversion processes or feeding interpretations.
Keywords: education; religion; conversion; minoritary cults; beliefs; resignificance